2014
DOI: 10.2337/dc13-2727
|View full text |Cite|
|
Sign up to set email alerts
|

The Relationship Between Alcohol Consumption and Vascular Complications and Mortality in Individuals With Type 2 Diabetes

Abstract: OBJECTIVEModerate alcohol consumption has been associated with a reduced risk of mortality and coronary artery disease. The relationship between cardiovascular health and alcohol use in type 2 diabetes is less clear. The current study assesses the effects of alcohol use among participants in the Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified-Release Controlled Evaluation (ADVANCE) trial. RESEARCH DESIGN AND METHODSThe effects of alcohol use were explored using Cox regression models, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 28 publications
2
83
2
1
Order By: Relevance
“…Moreover, current drinkers were more likely to have comorbidities and CVD -a finding that is probably debatable. Blomster provided evidence that patients with T2DM who drink alcohol moderately have a lower risk of CVD and microvascular complications compared with those who do not drink at all [34]. Temperate drinking appears to be a protective factor against diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, current drinkers were more likely to have comorbidities and CVD -a finding that is probably debatable. Blomster provided evidence that patients with T2DM who drink alcohol moderately have a lower risk of CVD and microvascular complications compared with those who do not drink at all [34]. Temperate drinking appears to be a protective factor against diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…An alcohol-induced increase in HDL cholesterol together with the antithrombotic effects of decreased fibrinogen, anti-inflammatory effects and increased adinopectin have been invoked as the major conduits for this decrease in CAD risk [33]. A prospective study in participants with type 2 diabetes similarly observed a 17% decrease in cardiovascular events with the consumption of up to 2-3 standard drinks/day, with red wine the predominant alcoholic beverage associated with the decrease in CAD risk [13]. If alcohol as red wine in the dose range we utilized does not raise HDL cholesterol or reduce fibrinogen levels it brings into question whether such effects are also important in reducing CAD risk in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, heavier alcohol intake, irrespective of beverage type, has been linked to increased blood pressure (BP) [7], triglycerides [8], homocysteine levels [9], arterial stiffness [10], and incidence of the metabolic syndrome [11]. Such contrasting influences may explain, at least in part, why there is a U-shaped relationship between alcohol consumption and incidence of coronary artery disease (CAD) [12], a pattern also seen in type 2 diabetes [13]. More information on the balance of effects of regular mild-to-moderate alcohol consumption on cardiovascular risk factors in type 2 diabetes is, therefore, of considerable public health interest.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate wine consumption is also related to a lower risk of diabetes mellitus 16,17 , cardiometabolic complications in diabetic patients 18,19 , and declining cognitive function 20,21 .…”
Section: Introductionmentioning
confidence: 99%